Republic of Turkey (Washington, D.C.)
3 mikrofiş (1. mikrofiş (49 poz ; 41 s.) ; 2. mikrofiş (32 poz ; s. 42-68) ; 3. mikrofiş (5 poz))
Keywords: In the 1973 volume, statistical tables cover the following topics: population, education, labor, national income, price indexes, agriculture, industry and mining, transportation, foreign commerce, foreign capital investments, finance, and U.S. economic assistance. Some tables present comparative figures for certain time periods (e.g., 1962-72, 1955-71, 1927-70).